Determinants Of Financial Performance In The Industrial Firm With The Moderating Role Of Size - Ghazala Benish , Dr.Naveed Hussain Shah , Dr.Muhmmad Rizwan Kamran , Sarfaraz Khan , Umer Ruqia Saadat , Nazim Ali (Migration Letters, 2024)
The study examines how firm growth and leverage affect financial performance in industrial firms, considering firm size as a moderator. To analyze this phenomenon, the data has been gathered from the State Bank of Pakistan website during the study period of 2014-2023. After the diagnostic tests, the most appropriate model of the regression model was used i.e. Random effect model. The findings of the study reveal that company growth (+) and leverage (-) significantly affect Firm Performance. The size moderates the relationship between growth and performance and leverage and FP. The moderation changes the relationship so it is the substitution effect. The study recommended that top management should go for leverage as size changes the relationship between leverage and profitability.